Igniting and resolving content disagreements during team interactions: A statistical discourse analysis of team dynamics at work. (15th December 2017) - Lehmann‐Willenbrock, Nale; Chiu, Ming Ming
Summary: Disagreements are integral to fruitful team collaboration but have rarely been studied within actual team interactions. We develop a temporal account of how disagreement episodes begin and are resolved during team interactions, testing explanatory factors at multiple levels: team context (team conflict states and team productivity), individual characteristics and perceptions (individual status and perceptions of team viability), and behavioral patterns (problem solving versus off‐task communication) with a statistical discourse analysis of 32, 448 turns of talk by 259 employees during 43 team meetings. As hypothesized, problem‐solving behaviors (e.g., describing problems and proposing solutions) ignited content disagreements, often by participants who perceived greater team viability. In contrast, after off‐task behaviors or talk by higher status team members, participants started fewer content disagreements. Moreover, content disagreements started by higher status individuals were more likely than those started by others to be resolved with agreements, especially via agreements with higher status individuals. Also, problem‐solving behaviors facilitated the resolution of disagreement episodes with agreement, whereas off‐task behaviors hindered them. Contrary to our hypotheses, team conflict states and productivity were not linked to starting or ending disagreements. We discuss the conceptual and methodological importance of capturing team interaction dynamics at work and derive practical implications for managing content disagreement.